Spatial data analysis with R programming for environment - Kaya, Efdal; Agca, Muge; Adiguzel, Fatih; Cetin, Mehmet (Informa UK Limited, 2018)
The use of open source software, which has been constantly evolving since the mid-2000s, has affected every research discipline. Disciplines using geographic information systems (GIS) and remote se...
Keywords: 13. Climate action; 14. Life underwater